Expanding Competitive Advantage Through Knowledge Sharing, Collaboration, and Organizational Innovation (Case Study: Mojan Food Industries Company) - Sardashti, Soroush (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: This study aims to examine the impact of knowledge sharing, collaboration, and organizational innovation on achieving a sustainable competitive advantage in the Mojan Food Industries Company. Methodology: The research employed a quantitative approach using structural equation modeling (SEM) to analyze the relationships between key variables. Data were collected through a structured questionnaire distributed to employees of Mojan Food Industries, with a total sample size of 295 respondents. The study measured knowledge sharing, collaboration, organizational innovation, and competitive advantage using validated scales. Data analysis was conducted using Smart PLS software to assess reliability, validity, and path coefficients. Findings: The results indicate a significant positive relationship between knowledge sharing and competitive advantage (β = 0.347, t = 8.273), knowledge sharing and organizational innovation (β = 0.571, t = 13.324), and knowledge sharing and collaboration (β = 0.769, t = 20.469). Additionally, organizational innovation positively influences competitive advantage (β = 0.292, t = 7.669), and collaboration enhances competitive advantage (β = 0.311, t = 7.116). These findings suggest that organizations can strengthen their competitive position by fostering a knowledge-sharing culture, encouraging collaborative practices, and prioritizing innovation. The model’s R² values (0.763 for competitive advantage, 0.667 for innovation, and 0.592 for collaboration) confirm its strong explanatory power. Conclusion: The study confirms that knowledge sharing, collaboration, and organizational innovation are essential drivers of competitive advantage. Organizations that invest in structured knowledge-sharing mechanisms, collaborative environments, and innovation initiatives are better positioned to sustain market leadership. The findings underscore the need for companies to integrate these factors into their strategic frameworks to achieve long-term success in competitive markets.